PHOSPHORUS-METABOLISM AND INTRACELLULAR PH IN THE HALOTOLERANT ALGA DUNALIELLA-PARVA STUDIED BY P-31-NMR - Ginzburg, M; Ratcliffe, R; Southon, T (1988)
The metabolism of the green unicellular halotolerant alga Dunaliella parva was studied by means of 31P nuclear magnetic resonance spectroscopy. The major soluble phosphate compounds were found to be similar to those in other organisms but two phosphodiesters, glycerophosphorylglycerol and glycerophosphorylcholine, were identified in algal tissue for the first time. Only a single pool of intracellular orthophosphate was observed and the chemical shift of the corresponding resonance was used to monitor the intracellular pH. The cell pH and the orthophosphate content were sensitive both to the oxygenation of the cells and to the illumination of the cell suspension. The intracellular pH was controlled over an external pH range of 6-9, but at pH 5 the cell contents became acidic. Carbonyl cyanide p-trifluoromethoxyphenylhydrazone was observed to uncouple oxidative phosphorylation but it did not equilibrate the pH difference across the cell membrane in experiments conducted at an external pH of 7.8. © 1988.